Corneal endothelial cell abnormalities in X-linked Alport syndrome. (2nd January 2020) - Nicklason, Eleanor; Mack, Heather; Beltz, Jacqueline; Jacob, Julie; Farahani, Mina; Colville, Deb; Savige, Judy
ABSTRACT: Background : X-linked Alport syndrome results from the effect of COL4A5  mutations on basement membranes in the kidney, ear and eye. This study investigated individuals with X-linked Alport syndrome for corneal abnormalities. Patients and Methods : Six men and four women from 8 families with genetically-diagnosed X-linked Alport syndrome underwent ophthalmological examination including slit lamp examination and corneal endothelial specular microscopy. Results for corneal microscopy for men and women with X-linked disease were compared separately with the mean values for age- matched normals using the student's t test. Results : Five of the 6 men had end-stage kidney failure, all 6 had a hearing loss, three had lenticonus, and three had a central fleck retinopathy. Two men had a history of recurrent corneal erosions but no evidence of posterior polymorphous corneal dystrophy. None of the four women had kidney failure, but two had a hearing loss, and two had a central fleck retinopathy. One woman, whose son had recurrent corneal erosions, also had erosions, but no features of a posterior polymorphous corneal dystrophy. Corneal specular microscopy demonstrated abnormalities in affected men and women, with larger endothelial cells ( p = .0001 in men, p = .004 in women) fewer 6-sided cells ( p = .0001, p = .001 respectively) and reduced cell density ( p = .03, p = .02 respectively) than normal. Conclusions : Recurrent corneal erosions are common in men and women with X-linked Alport syndrome, but posterior polymorphous corneal dystrophy is rare. The abnormal corneal endothelial cells in affected men and women are consistent with an abnormal Descemet membrane, and the reduced cell density resembles the reduced podocyte numbers found in the Alport glomerulus.